Rethinking sport science to improve coach-researcher interactions - Loturco, I. (International Journal of Sports Physiology and Performance, 2023)
A typical comment made by coaches in high-performance sport is "I avoid interactions with researchers because they often fail to effectively address the issues that impact my daily work." Moreover, it is not uncommon to hear statements like "I don`t utilize the scientific services offered by my club because conclusions and recommendations are vague and abstract" or "Results lack clarity and the methods employed are too complex to be implemented at the speed and scale required in my professional context." In contrast, it is also common to come across sport scientists expressing concerns regarding the limited openness exhibited by practitioners. Complaints such as "Coaches appear resistant to adopting new concepts" or "Despite being informed, they continue to use inappropriate techniques" are frequently reiterated. Notably, these critiques have endured since my early days as an undergraduate student, and they still seem to be far from resolved. This is why coach-scientist relationships remain a key issue to be tackled and overcome.